13C magnetic resonance spectroscopic imaging of hyperpolarized [1‐13C, U‐2H5] ethanol oxidation can be used to assess aldehyde dehydrogenase activity in vivo. Issue 5 (6th May 2014) - Dzien, Piotr; Kettunen, Mikko I.; Marco‐Rius, Irene; Serrao, Eva M.; Rodrigues, Tiago B.; Larkin, Timothy J.; Timm, Kerstin N.; Brindle, Kevin M.
Abstract : Purpose: Aldehyde dehydrogenase (ALDH2) is an emerging drug target for the treatment of heart disease, cocaine and alcohol dependence, and conditions caused by genetic polymorphisms in ALDH2. Noninvasive measurement of ALDH2 activity in vivo could inform the development of these drugs and accelerate their translation to the clinic. Methods: [1‐ 13 C, U‐ 2 H5 ] ethanol was hyperpolarized using dynamic nuclear polarization, injected into mice and its oxidation in the liver monitored using 13 C MR spectroscopy and spectroscopic imaging. Results: Oxidation of [1‐ 13 C, U‐ 2 H5 ] ethanol to [1‐ 13 C] acetate was observed. Saturation of the acetaldehyde resonance, which was below the level of detection in vivo, demonstrated that acetate was produced via acetaldehyde. Irreversible inhibition of ALDH2 activity with disulfiram resulted in a proportional decrease in the amplitude of the acetate resonance. Conclusion: 13 C magnetic resonance spectroscopy measurements of hyperpolarized [1‐ 13 C, U‐ 2 H5 ] ethanol oxidation allow real‐time assessment of ALDH2 activity in liver in vivo. Magn Reson Med, 2014. © The Authors. Magnetic Resonance in Medicine Published by Wiley Periodicals, Inc. on behalf of International Society of Medicine in Resonance. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution, and reproduction in any medium, provided the original work is properly cited. Magn Reson Med 73:1733–1740, 2015. © 2014 Wiley Periodicals, Inc.